FAKTOR-FAKTOR YANG MEMENGARUHI PPh BADAN TERUTANG PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - RIAN SUMARTA; AULIA ULMAH INTAN (Media Bisnis, 2020)
The purpose of this research is to obtain the factors that affect the corporate income tax. The independent variables of this research are capital structure (DER), profitability (ROA), operating cost, net sales, commercial expense, and luquidity ratio. The dependent variable in this research is corporate income tax. In this following research, the researchers used manufacture companies listed in Indonesia Stock Exchange from 2016-2018 which had 492 data from 164 companies. Based on criteria there are 177 data from 59 companies. The data was analyzed by using multiple regression analysis with IBM SPSS 19 version. The results of this research indicated that profitability (ROA), operating cost, and net sales have influence significant toward corporate income tax Minimizing operating costs in the company can affect the profitability ratio and can increase company profits. Company profit comes from sales made by the company, profit is one of the tax objects, so that the amount of company profit can determine the amount of corporate income tax owed. However capital structure (DER), comercial expense, and liquidity ratio have no influence toward corporate income tax.